2021
DOI: 10.1371/journal.pone.0254519
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between staphylococcal enterotoxins A and D and superantigen-like proteins 1 and 5 for predicting methicillin and multidrug resistance profiles among Staphylococcus aureus ocular isolates

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) and multidrug-resistant (MDR) S. aureus strains are well recognized as posing substantial problems in treating ocular infections. S. aureus has a vast array of virulence factors, including superantigens and enterotoxins. Their interactions and ability to signal antibiotics resistance have not been explored. Objectives To predict the relationship between superantigens and methicillin and multidrug resistance among S. aureus ocular isolates. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Moreover, the coexistence rate of the mecA and blaZ genes in S. Sciuri was extremely high (> 90%) in this study, compared to a previous study [71], raising serious concern for AMR in this species because the mecA and blaZ genes coexist often in other staphylococci species, including S. pseudintermedius and S. aureus [72][73][74][75][76]. The majority of MRSS in this study also had an MDR phenotype which is rarely reported; MDR staphylococci are mainly S. aureus [77][78][79][80]. MRSS carrying multiple AMR genes might threaten animal and human health because this pathogen is capable of causing a variety of diseases and transmit AMR genes to other staphylococci [43][44][45][46][47][53][54][55].…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, the coexistence rate of the mecA and blaZ genes in S. Sciuri was extremely high (> 90%) in this study, compared to a previous study [71], raising serious concern for AMR in this species because the mecA and blaZ genes coexist often in other staphylococci species, including S. pseudintermedius and S. aureus [72][73][74][75][76]. The majority of MRSS in this study also had an MDR phenotype which is rarely reported; MDR staphylococci are mainly S. aureus [77][78][79][80]. MRSS carrying multiple AMR genes might threaten animal and human health because this pathogen is capable of causing a variety of diseases and transmit AMR genes to other staphylococci [43][44][45][46][47][53][54][55].…”
Section: Discussionmentioning
confidence: 47%
“…S. aureus strains isolated from atopic patients experiencing keratoconjunctivitis with corneal ulceration, possessed enterotoxins more frequently compared to patients with no ulceration [ 56 ]; the role of enterotoxins in ocular infections remains to be fully defined. Another study found enterotoxin and enterotoxin-like genes were found to be highly correlated with MRSA and predictive for MDR status in ocular isolates [ 57 ]. The antibiotic susceptibility data of the isolates used in the current study shows that most of the strains were multi-drug resistant (MDR) [ 12 ], so the distribution of enterotoxin-like genes in 28% of MRSA USA infectious strains (MK + conjunctivitis) may indicate their MDR status, but the presence of enterotoxin-like genes in MSSA (methicillin sensitive S. aureus ) MDR strains from other conditions indicates enterotoxin genes are probably associated with the source of isolation.…”
Section: Discussionmentioning
confidence: 99%
“…A weighted chi-squared test was used for the descriptive overview of each predictor. Random Forest [ 40 ] model was applied for the multivariate classification analysis, which is a modern machine learning technique that has been utilized to select replicable sets of exploratory factors from a large number of predictors [ 42 47 ]. Because this method is completely nonparametric without any restrictive underlying model assumptions, nonlinear and complex interrelationships can be robustly accounted for.…”
Section: Methodsmentioning
confidence: 99%